The Accumulation of Risk and Essential Elements in Edible Mushrooms Chlorophyllum rhacodes, Suillus grevillei, Imleria badia, and Xerocomellus chrysenteron Growing in the Czech Republic - Šíma, Jan; Vondruška, Jan; Svoboda, Lubomír; Šeda, Martin; Rokos, Lukáš (Chemistry and biodiversity, 2019)
Risk and essential elements were determined in fruiting bodies of wild growing edible mushrooms Chlorophyllum rhacodes, Suillus grevillei, Imleria badia, and Xerocomellus chrysenteron collected in an unpolluted site in South Bohemia, the Czech Republic. The elements were also determined in underlying soils and the bioconcentration factors were calculated. The analyses revealed that C. rhacodes accumulated Ag, Cu, Rb, Se, Zn, As, Cd, and Tl. On the other hand, S. grevillei accumulated Cd, Rb, Ag, Se, and Cs. I. badia and X. chrysenteron strongly accumulated Rb, Cs, and Ag; these species showed the ability to accumulate Cu and Zn as well. Contents of detrimental CrVI were in all cases below the quantification limit (0.003 mg kg-1 dry matter). Studied mushroom species (mainly C. rhacodes) accumulated some toxic elements. However, no considerable effect on human health is expected since they are usually consumed as a delicacy and do not represent a major component of diet.
Keywords: plodnice hub; Agaricales; Česká republika; Trace Elements; Fruiting Bodies, Fungal; hodnocení rizik; stopové prvky; Czech Republic; Plants, Edible; jedlé rostliny; Risk Assessment